THE INFLUENCE OF TEACHER PROFESSIONALITY AND CREATIVITY IN USING LEARNING MEDIA ON THE ARABIC LANGUAGE LEARNING OUTCOMES OF CLASS VIII STUDENTS OF MTS PONDOK PESANTREN DARUL ISTIQAMAH SOUTH LAPPA'E SINJAI - ifa, Musyarifah (JICSA : Journal of Islamic Civilization in Southeast Asian, 2023)
Abstract This article discusses the influence of teacher professionalism and creativity in using learning media on students' Arabic learning outcomes. A teacher must have a great ability to learn, to be able to play the role of a presenter, guide and evaluator, a teacher must have adequate knowledge, not only knowledge and expertise, but also experience, in analyzing this article using the type of research is quantitative, with instruments collecting data through questionnaires, observations and tests, the research results show that (1) the professionalism of Arabic teachers in using media in class VIII MTs Darul Istiqamah Lappa'e is in the medium category; (2) the creativity of Arabic teachers in using media in class VIII MTs Darul Istiqamah Lappa'e is in the medium category; (3) the learning outcomes of class VIII MTs students are in the medium category; (4) there is no partial influence on the professionalism of teachers using media on the Arabic language learning outcomes of class VIII students at MTs Darul Istiqamah Lappa'e and the coefficient of determination is 0.004; (5) there is no partial influence of teacher creativity using media on the Arabic language learning outcomes of class VIII MTs Darul Istiqamah Lappa'e students with a coefficient of determination of 0.010; (6) there is no simultaneous influence of teacher professionalism and creativity using media on the Arabic language learning outcomes of class VIII students at MTs Darul Istiqamah Lappa'e, and the coefficient of determination is 0.015.